2005
DOI: 10.1089/neu.2005.22.966
|View full text |Cite
|
Sign up to set email alerts
|

Serum Hsp70 as an Early Predictor of Fatal Outcome after Severe Traumatic Brain Injury in Males

Abstract: Severe traumatic brain injury (TBI) is associated with a 35-70% mortality rate. Biochemical markers of cellular stress/injury have been proposed to indicate outcome after head injury. Therefore, our aim was to determine whether Hsp70 could be detected in the serum of patients after severe TBI and whether serum levels of Hsp70 correlate with primary outcome in severe TBI. Twenty consecutive male patients, victims of severe TBI (GCS 3-8), were enrolled in this prospective study. Clinical outcome variables of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 41 publications
1
30
0
2
Order By: Relevance
“…For example, increased extracellular Hsp70 levels are noted following strenuous exercise (180,181,(204)(205)(206)(207)(208), following cardio-pulmonary bypass in both adults (209,210) and children (Wheeler, unpublished data), in elderly adults (211,212), and in children with acute lung injury (Wheeler, unpublished data). In addition, increased extracellular Hsp70 concentrations correlate with worse outcome in a variety of inflammatory disease processes, including liver disease (213), coronary artery disease (214)(215)(216)(217), traumatic brain injury secondary to child abuse (218), pre-eclampsia (219), sickle cell disease vasoocclusive crisis (220), septic shock (221), and traumatic brain injury (222). Conversely, increased extracellular Hsp70 levels correlated with improved outcome following multiple trauma in adults (141).…”
Section: Stress Proteins and Innate Immunitymentioning
confidence: 99%
“…For example, increased extracellular Hsp70 levels are noted following strenuous exercise (180,181,(204)(205)(206)(207)(208), following cardio-pulmonary bypass in both adults (209,210) and children (Wheeler, unpublished data), in elderly adults (211,212), and in children with acute lung injury (Wheeler, unpublished data). In addition, increased extracellular Hsp70 concentrations correlate with worse outcome in a variety of inflammatory disease processes, including liver disease (213), coronary artery disease (214)(215)(216)(217), traumatic brain injury secondary to child abuse (218), pre-eclampsia (219), sickle cell disease vasoocclusive crisis (220), septic shock (221), and traumatic brain injury (222). Conversely, increased extracellular Hsp70 levels correlated with improved outcome following multiple trauma in adults (141).…”
Section: Stress Proteins and Innate Immunitymentioning
confidence: 99%
“…HSP70 was rapidly released into the circulation after myocardial infarction and the HSP70 levels correlated with the levels of troponin T and creatine kinase MB (Dybdahl et al 2005).The present study is similar, because in the background of cardiac arrest acute myocardial infarction was established in 85 % of patients, confirming that HSP70 is rapidly elevated after myocardial injury. Finally, elevated serum HSP70 levels in patients with severe traumatic brain injury were shown to predict poor outcomes (da Rocha et al 2005). These studies aggregately confirm that extracellular HSP70 is detectable in various forms of stress, and might gain wide acceptance in predicting the prognosis or determining risk status in the diseases mentioned above.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, Hecker et al reviewed the potential of HSP70 as a biomarker for the rapid detection of brain and spinal cord ischemia (Hecker and McGarvey 2011). Elevated serum HSP70 levels of patients with severe traumatic brain injury predicted death within 20 h after injury (da Rocha et al 2005). Based on the foregoing, we hypothesized that HSP70 might prove not only a reliable biomarker of neuronal damage, but also a good surrogate of endothelial-cell activation and death, as well as of inflammatory reaction in post-cardiac-arrest patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the brain, Hsp70 may be induced by a series of pathological stimuli including ischemia, exitotoxicity and inflammatory responses. (73) Pittet et al (74) showed that the Hsp72 (member of the Hsp70 family) can be detected in the serum of patients with severe trauma within 30 minutes after trauma and that high levels are associated with favorable outcome after trauma. Recently we investigated the role of the Hsp70 protein as a predictive marker of mortality for severe TBI in men.…”
Section: Cellular Stress Proteinsmentioning
confidence: 99%
“…We proved that high serum levels of Hsp70 may be a promising biomarker for cases of severe TBI. (73) …”
Section: Cellular Stress Proteinsmentioning
confidence: 99%